If You Can Solve This, You Are Truly Brilliant! 2 of X

Calculus Level 4

0 t 1 2 e 1985 ( t + t 1 ) d t \large \int_{0}^{\infty}t^{-\frac{1}{2}}e^{-1985(t+t^{-1})}dt

Evaluate the integral above. You may assume that e x 2 d x = π \displaystyle \int_{-\infty}^{\infty}e^{-x^2}dx =\sqrt{\pi} .

π 1985 e 3985 \sqrt{\frac{\pi}{1985}}e^{-3985} π 1985 e 3970 \sqrt{\frac{\pi}{1985}}e^{-3970}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Hasan Kassim
Apr 14, 2018

0 1 y e ( a y + b y ) d y = π b e 2 a b \displaystyle \int_0^{\infty} \frac{1}{\sqrt{y}} e^{-(\frac{a}{y} + by ) } dy = \sqrt{\frac{\pi}{b}} e^{-2\sqrt{ab}}

P r o o f : \mathbf{Proof \; : }

A = 0 1 y e ( a y + b y ) d y \displaystyle A= \int_0^{\infty} \frac{1}{\sqrt{y}} e^{-(\frac{a}{y} + by ) } dy

= y a b y a b 0 1 y e a b ( 1 y + y ) d y \displaystyle \overset{{\color{#D61F06}{y \to \sqrt{\frac{a}{b}} y }} }{=} \sqrt{\sqrt{\frac{a}{b}}} \int_0^{\infty} \frac{1}{\sqrt{y}} e^{-\sqrt{ab} ( \frac{1}{y}+y)} dy

= y 1 y a b 0 1 y y e a b ( 1 y + y ) d y \displaystyle \overset{ {\color{#D61F06}{y \to \frac{1}{y} }} }{=}\sqrt{\sqrt{\frac{a}{b}}} \int_0^{\infty} \frac{1}{y\sqrt{y}} e^{-\sqrt{ab} ( \frac{1}{y}+y)} dy

Hence:

2 A = a b 0 ( 1 y + 1 y y ) e a b ( 1 y + y ) d y \displaystyle 2A = \sqrt{\sqrt{\frac{a}{b}}} \int_0^{\infty} \bigg( \frac{1}{\sqrt{y}} + \frac{1}{y\sqrt{y}} \bigg) e^{-\sqrt{ab} ( \frac{1}{y}+y)} dy

A = a b 0 ( 1 2 y + 1 2 y y ) e a b ( y 1 y ) 2 2 a b d y \displaystyle A = \sqrt{\sqrt{\frac{a}{b}}} \int_0^{\infty} \bigg( \frac{1}{2\sqrt{y}} + \frac{1}{2y\sqrt{y}} \bigg) e^{-\sqrt{ab} ( \sqrt{y} - \frac{1}{\sqrt{y}})^2 -2\sqrt{ab} } dy

= y 1 y y a b e a b y 2 2 a b d y \displaystyle \overset{{\color{#D61F06}{\sqrt{y} - \frac{1}{\sqrt{y}} \to y }}}{=} \sqrt{\sqrt{\frac{a}{b}}} \int_{-\infty}^{\infty} e^{-\sqrt{ab}y^2 - 2\sqrt{ab}} dy

This can be derived from the Gaussian Integral :

A = π b e 2 a b \displaystyle \boxed{A = \sqrt{\frac{\pi}{b}} e^{-2\sqrt{ab}} } .

Set a = b = 1985 a=b=1985 , you get the desired answer.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...